2017
DOI: 10.1007/s00216-017-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the fate and transport of secondary plant metabolites in a laboratory mesocosm experiment by employing mass spectrometric imaging

Abstract: Mass spectrometric imaging (MSI) has received considerable attention in recent years, since it allows the molecular mapping of various compound classes, such as proteins, peptides, glycans, secondary metabolites, lipids, and drugs in animal, human, or plant tissue sections. In the present study, the application of laser-based MSI analysis of secondary plant metabolites to monitor their transport from the grass leaves of Dactylis glomerata, over the crop of the grasshopper Chorthippus dorsatus to its excrements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…The conjugation with quinic acids is described here for the first time as part of a detoxification pathway. Quinic acid has been reported to play a role in response to herbivory (Wang et al 2016), and quinic acids were detected in the gut of insects (Crecelius et al 2017). It was also suggested that quinic acid conjugates like chlorogenic acid produce feeding-deterrent compounds after cleavage and oxidative transformation of the phenylpropanoic part (Stevenson et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The conjugation with quinic acids is described here for the first time as part of a detoxification pathway. Quinic acid has been reported to play a role in response to herbivory (Wang et al 2016), and quinic acids were detected in the gut of insects (Crecelius et al 2017). It was also suggested that quinic acid conjugates like chlorogenic acid produce feeding-deterrent compounds after cleavage and oxidative transformation of the phenylpropanoic part (Stevenson et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…36 Because of their structure, metabolites can have poor ionization efficiency, which has prompted the development of many derivatization schemes to increase access to metabolites in samples. 28,31,53 Just like lipids, a wide variety of ionization techniques lends well to metabolites, including MALDI, 12,14,20,28,29,31,36,137,233236 DESI, 2,218,237 and LAESI, 69 although, based upon citations alone, MALDI is by far the most popular. This is actually surprising, as most matrixes used for MALDI analysis are small organic compounds, meaning they can have their own interfering ions in the metabolite mass range at high concentrations, masking some possible signals of interest.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Furthermore, understanding the entire metabolic process of secondary metabolites in the plant–insect–soil system makes MSI more appealing. Crecelius et al () using LDI tracked the fate of secondary metabolites produced by grass ( Dactylis glomerate ), in grasshoppers ( Chorthippus dorsatus ) over the digestion process to its excrements and finally in the soil solution. The results showed that in the leaf wounds of plants, quinic acid, apigenin, and luteolin decreased after a day of feeding, whereas the flavonoids and rosmarinic acid increased.…”
Section: Insect–plant Interactionmentioning
confidence: 99%
“…MSI has been applied to insect tissue section for in situ characterization of three major aspects, endogenous metabolites (including lipids, neuropeptides, proteins, and defense compounds; Bhandari, Schott, Römpp, Vilcinskas, & Spengler, ; Catae et al, ; Ly et al, ; Marty et al, ), exogenous metabolites (drugs and insecticides; Ohtsu, Yamaguchi, Nishiwaki, Fukusaki, & Shimma, ; Olsen, Hansen, & Janfelt, ), and insect–plant interactions (tracking the fate of plant secondary defense compounds; Crecelius, Michalzik, Potthast, Meyer, & Schubert, ). How insects rapidly adapt to host plant, how insects are resistant to insecticides, and how insects interact with gut microbes have recently become hot topics in insect sciences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation